GAMBARAN KADAR KREATININ SERUM PADA PENDERITA HIPERTENSI YANG MENGONSUMSI OBAT ANTI HIPERTENSI DI WILAYAH KERJA PUSKESMAS TELAGA DEWA KOTA BENGKULU - Fitriany, Evi; Putri, Alya Annisa; Laksono, Heru; Halimatussa’diah, Halimatussa’diah (Ensiklopedia of Journal, 2025)
Abstract: Hypertension is an increase in blood pressure that causes the heart to work extra to pump blood. This causes the arteries around the kidney blood vessels to narrow and risks disrupting kidney function. People with hypertension are advised to take anti-hypertensive drugs to normalize blood pressure. Therefore, compliance in taking these drugs is required. Based on Riskesdas data in 2018, there were 32.3% of hypertensive patients who did not regularly take anti-hypertensive drugs and 13.3% did not consume them. One of the indicators used to determine impaired renal function is creatinine examination. This study aims to determine the description of serum creatinine levels in hypertensive patients who take anti-hypertensive drugs in the working area of the Telaga Dewa Health Center, Bengkulu City. This study uses descriptive method to obtain the results of the description of serum creatinine levels in hypertensive patients who take anti-hypertensive drugs in the working area of the Telaga Dewa Health Center, Bengkulu City. The results showed that out of 36 respondents, 8 people (22.2%) had high creatinine levels, 23 people (63.9%) had normal creatinine levels, and 4 people (13.9%) had low creatinine levels. Based on the research conducted, it can be concluded that there are a small proportion of samples that have high creatinine levels, most samples have normal creatinine and a small proportion have low creatinine levels.Keywords: Hypertension, Creatinine, Drug Anti Hypertension